2014
DOI: 10.1016/j.gaitpost.2013.06.003
|View full text |Cite
|
Sign up to set email alerts
|

Influence of long-term wearing of unstable shoes on compensatory control of posture: An electromyography-based analysis

Abstract: Purpose: This study investigated the influence of long-term wearing of unstable shoes (WUS) on compensatory postural adjustments (CPA) to an external perturbation.Methods: Participants were divided into two groups: one wore unstable shoes while the other wore conventional shoes for 8 weeks. The ground reaction force signal was used to calculate the anterior-posterior (AP) displacement of the centre of pressure (CoP) and the electromyographic signal of gastrocnemius medialis (GM), tibialis anterior (TA), rectus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 38 publications
1
15
0
Order By: Relevance
“…Finally, because these postural control adaptation strategies lead to reduced noise and increased accuracy (Lacquaniti et al, 1993), a decreased postural control system error, demonstrated through the CoM and CoP relation (Winter, 1995a) (RM and TR (Zatsiorsky & Duarte, 2000)) can also be expected. after prolonged use of the shoes, as no differences were previously demonstrated during compensatory postural adjustments in response to an external perturbation (Sousa et al, 2013a;Sousa et al, 2013b). Also, the results obtained in these studies support the hypothesis of a decreased co-activation command in the unstable shoe condition compared to barefoot.…”
Section: Introductionsupporting
confidence: 79%
See 3 more Smart Citations
“…Finally, because these postural control adaptation strategies lead to reduced noise and increased accuracy (Lacquaniti et al, 1993), a decreased postural control system error, demonstrated through the CoM and CoP relation (Winter, 1995a) (RM and TR (Zatsiorsky & Duarte, 2000)) can also be expected. after prolonged use of the shoes, as no differences were previously demonstrated during compensatory postural adjustments in response to an external perturbation (Sousa et al, 2013a;Sousa et al, 2013b). Also, the results obtained in these studies support the hypothesis of a decreased co-activation command in the unstable shoe condition compared to barefoot.…”
Section: Introductionsupporting
confidence: 79%
“…Indeed, the results of this study reveal that prolonged wearing of the unstable shoes led to a large effect in the increase of thigh antagonist co-activation. A transfer of postural control synergy for the thigh has been demonstrated in compensatory responses after a 8 weeks period of wearing unstable shoes (Sousa et al, 2014) and has been reported as more beneficial to optimise postural stability (Day et al, 1993;Horak et al, 1990;Kuo, 1993;Runge et al, 1999;Yang et al, 1990). This association is corroborated not only by the decrease of the most representative CoP displacement parameters and RM P-P, but also by decreased anterior-posterior TR RMS.…”
Section: Wearing Of the Unstable Shoes Led To A Higher Performance Anmentioning
confidence: 99%
See 2 more Smart Citations
“…Other applications also address gait signature analysis. For example, IMMUs are used to determine joint stress in barefoot running [64], landing patterns [30] and vertical loading [29,30,35,45,[65][66][67][68], loading while running barefoot [69], the effects of a high-heeled gait [70], the effects of rollover footwear [71], and the influence of the long-term wearing of unstable shoes [67].…”
Section: Sports and Healthy Living Applicationsmentioning
confidence: 99%